Indonesian in Service Teacher’s Production of Directive Speech Acts and Students’ Responses - Alfi Nur Azizah; Suparno Suparno; Slamet Supriyadi (RIRAI Publisher, 2020)
Teacher uses language as a medium of communication to teach, guide and instruct students in the classroom. This study aims to investigate the English teacher's directives and the students' responses to these directives. This study participants were an English teacher of a junior high school in Indonesia who teaches an eighth-grade class and her students who were chosen purposively. This qualitative case study was collected through observation, and interviews and were then analyzed by following Miles' interactive cyclical model. The results revealed that the teacher mostly produced directive speech acts types of commands and requests rather than suggestions. Commands have been the most commonly used type of directives since the teacher plays a control in the classroom because it is more understandable and familiar for the students. Hence, the students' responses varied, and depended on their response strategies and each personal reason.